Cevaplar

En İyi Cevap!
2012-10-28T00:17:41+03:00

uzun kenara ''a'' diyelim kısa kenar a-√12 olur  a-√12 = a-2 √ 3 ( √12 =  √4*3)

2a+ 2(a - 2 √3)= 8 √3

2a + 2a - 4 √3 = 8 √3

4a-4 √3= 8 √3

4a = 12 √3 

   a = 3 √3       uzun kenar= 3 √3       kısa kenar = 3 √3 - 2 √3 =  √3

 

alan = uzun kenar * kısa kenar          3 √3 *  √3 = 3*3 = 9                                   

1 5 1
2012-10-28T00:45:22+03:00

kısa kenar : x

uzun kenar : x+\sqrt{12}

2x + 2(x+\sqrt{12})=8√3

2x+2x+2\sqrt{12}=8√3

4x+4√3=8√3

4x=4√3

x=√3 (yani kısa kenar)

A = √3 . (√3+√12)

parantezi dağıtacağız.

A = (√3.√3) + (√3.√12)

A = 3+√36

3+6

9

1 5 1